2008
DOI: 10.1016/j.hrthm.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A computer modeling tool for comparing novel ICD electrode orientations in children and adults

Abstract: Background-ICD implants in children and patients with congenital heart disease are complicated by body size and anatomy. A variety of creative implant techniques have been utilized empirically in these groups on an ad hoc basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…Alternative subcutaneous placement strategies have been proposed recently [3], which allow a much wider range of feasible lead placements. However, the rationalization of lead placements is challenging [9]. In all scenarios which are currently considered, currents are injected via a sparse set of small electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative subcutaneous placement strategies have been proposed recently [3], which allow a much wider range of feasible lead placements. However, the rationalization of lead placements is challenging [9]. In all scenarios which are currently considered, currents are injected via a sparse set of small electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in animal experiments and human studies, it has been shown that the voltage gradients in the heart are lower during S-ICD defibrillation as compared to transvenous ICD defibrillation; S-ICD defibrillation is also not associated with troponin release. (13)(14)(15)(16) Nevertheless, the S-ICD system is not without its disadvantages. When compared to transvenous ICD systems, S-ICD systems can only provide backup pacing following a shock, as pacing from the subcutaneous position invariably causes painful muscle stimulation.…”
Section: A 4bmentioning
confidence: 99%
“…Therefore, S-ICD systems cannot provide antitachycardia pacing to painlessly terminate VT. In addition, as the energy needed by the S-ICD system to defibrillate is approximately three-fold higher than that needed by transvenous ICD systems, (13,14) the pulse generator of the S-ICD system is more bulky than the current generation of transvenous ICD systems. (17,18) It measures 78 mm × 65 mm × 15 mm, with a volume of 69 cc and a mass of 145 g, which is almost twice the size of a traditional ICD.…”
Section: A 4bmentioning
confidence: 99%
“…[24][25][26][27][28] Each of these patient-specific adaptations, however, still required some form of transvenous or epicardial sensing electrodes. Also, these were primarily adapted to developments in patient clinical status, surgical limitations or lead failures, and the clinically limited options to repair the previously implanted intrathoracic defibrillation lead system.…”
Section: Prelude To First Use Of Stand-alone Subcutaneous Defibrillatormentioning
confidence: 99%